Hypersensitivity Pneumonia Due to Lentil Aspiration: A Rare but Painstaking Pulmonary Illness - Md. Abid Hossain Mollah FCPS; Jebun Nahar MD; Priya Purakayostho MBBS; Nabila Tabassum MRCPCH; Tasnima Ahmed FCPS; Sherin Khan FCPS; Sabrina Jashim FCPS; Mohammod Jobayer Chisti PhD (Global Pediatric Health)
A 7-month-old girl had been suffering from progressively deteriorating pneumonia despite getting multiple courses of broad-spectrum antibiotics as well as anti-fungal drugs for adequate duration. To find out the cause behind this deterioration, the patient underwent thorough clinical and relevant laboratory evaluation including chest radiology & imaging, screening for primary immune deficiency disorders (PID), cystic fibrosis, tuberculosis, invasive fungal pneumonia, congenital heart disease, covid pneumonia, TORCH etc. but failed to solve the mystery. Upon further detailed re-evaluation, it was discovered that the child had a history of being forcefully fed lentil-based khichuri (a rice-lentil mixed dish) during her weaning process and diagnosis was finally confirmed as hypersensitive pneumonia due to lentil aspiration by a high level of IgG, specific to lentil antigen. Treatment was commenced with prednisolone resulting in significant improvement in her clinical and radiological condition within 72 hours.